UNDERSTANDING THE CONCEPT OF COMMUNITY-BASED ENTREPRENEURSHIP: A SYSTEMATIC REVIEW APPROACH - HASSAN, FATIMAH; DAHALAN, NORZIANI; HILMI, MOHD FAIZ; JAAFAR, MASTURA (The journal of contemporary issues in business and government, 2021)
Community-based entrepreneurship is a growing concept in entrepreneurship research, which capitalises on the demand for community participation in any enterprise development. However, there are many misconceptions from the previous researchers regarding the terms’ definition and influencing factors. This paper aims to understand community-based entrepreneurship concepts and add value to the current literature in an academic context. This paper employed secondary data resources from 2010 until 2020. Four scientific databases are selected as an appropriate database, and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method was employed as the basic method for conducting this review. Based on 14 articles which were reviewed thoroughly and systematically, this paper found the definition of community-based entrepreneurship and summarised two main factors that influenced the success of community-based entrepreneurs. Overall, this systematic review provides a good platform for further research by identifying the research needs in community-based entrepreneurship.